(untitled) (Journal of Comilla Medical College Teachers’ Association, 2024)
Background: Extrahepatic portal venous obstruction accounts for 80% of cases of portal hypertension. Of all cases of portal hypertension (PHT) in developing countries, 40% are due to portal vein thrombosis. No risk factors were found in most of the cases of extrahepatic portal hypertension. To date, numerous observational studies have reported the prevalence of antithrombin III deficiency in patients with portal vein thrombosis. In Bangladesh, a largely populated country, we see a good number of patients with EHPVO every year. But there is a lack of such studies in our country about the frequency of antithrombin III deficiency. Objective: To find out the frequency of antithrombin III deficiency in children with extrahepatic portal hypertension. Methods: Over a period of 18 months, this cross-sectional descriptive study was carried out at the Department of Paediatric Gastroenterology and Nutrition of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh. Children of either gender diagnosed with cases of extrahepatic portal hypertension were included in this study. Informed written consent was obtained from the parent/caregiver of each child. Data were analyzed by using SPSS 22.0 for Windows 10 (SPSS, Inc, Chicago, IL). In all cases, the significance level of p value was <0.05. Results: A total of 18 patients diagnosed with extrahepatic portal hypertension were enrolled in this study, out of which 14 (78%) were males. The mean age at presentation was 8.6 ± 4.7 years. The most common (83%) presenting symptom was upper gastrointestinal bleeding manifested as hematemesis and melena. On physical findings, the majority (89%) of patients were pale, splenomegaly was present in 83% of patients. On full blood count, anemia was present in all (100%) patients, leucopenia in 4 (22.2%), and thrombocytopenia in 14 (78%) patients. Cavernous transformation was found in 9 (50%) patients, portal vein thrombosis (PVT) was identified in one (5.6%) patient. All (100%) patients had esophageal varices. Nine (50%) patients had Antithrombin III deficiency. Conclusion: Antithrombin III deficiency was seen in half (50%) of the studied patients. No significant difference or association was identified between the antithrombin III deficient with the normal group in terms of clinical profile, biochemical parameters, and endoscopic findings. J Com Med Col Teachers’ Asso July 2023; 27(2): 45-51